User-Centered Computer Aided Language Learning - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2006)
In the field of computer aided language learning (CALL), there is a need for emphasizing the importance of the user. User-Centered Computer Aided Language Learning presents methodologies, strategies, and design approaches for building interfaces for a user-centered CALL environment, creating a deeper understanding of the opportunities and challenges of the field. User-Centered Computer Aided Language Learning acts as a guide to help educators, administrators, professionals and researchers find the basis of a framework for the development and management of CALL environments that are enriched with many domains and take into account interaction and activity, which go beyond the basic linguistic elements of the field.